Community Participation thru Eco Scuba Tourism A case study : Koh Tao, Phangan, Surathanee Province - Damrongsiri, Thumrongsak; Vivanichkul, Narasri (Mekong-Salween Civilization Studies Journal, 2016)
This article “The Community Participation thru Scuba Tourism” arose from a part of the preliminary study of larger a doctorate study entitled “A Model of Development Eco Scuba Tourism Management in Gulf of Thailand” The objective of this research was to study about the participation of community, entrepreneur and government thru Eco Scuba Tourism Program (EST.) Qualitative research was used as a core methodology. An in-depth interview was also conducted with the government and private sectors, by employing a list of structured questions. The data analysis was finally based on a narrative and content analysis. The result was found that Koh Tao is the most popular destination for scuba divers and it is the top place for training and developing a certified scuba diver (Tourism Authority of Thailand, 2015.) Scuba tourism and all related businesses i.e. hotels, resorts sand and restaurants generate a significant income to the community. The community participation in Eco Scuba Tourism is very important to preserve tourism natural resource. Mixed populations in Koh Tao such as indigenous, immigrants, alien labor forces, and tourists that obstructs the promotion of the EST. The community participation is a joint effort between government sector and private sector. The public sector plays a key role in issuing rules and regulations, putting an integrated plan to manage the polluted water, garbage, traffic, and infrastructure, and directing the municipality. The private sector focuses on strengthening the collaboration of the community. For example, set up “Save Koh Tao Club,” replace foam food boxes with paper food containers, creating a bouncy world for beginning diver to preserve natural resources, producing and use a bio soaps and shampoos which is friendly and protect the environment. Developing the right consciousness to the community in preserving the environment is very critical as it helps promoting the preservation of marine resources sustainably.